PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA FLASHCARD DIGITAL TERHADAP HASIL BELAJAR KOGNITIF IPA SISWA SEKOLAH DASAR - Sakinah, Lisna; Nuraeni, Fitri; Yogiarni, Tiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning process is a series of prepared or designed processes to teach students, implemented, and systematically assessed to achieve learning goals productively and optimally. Therefore, the learning process conducted should be optimal. This research utilizes a quasi-method with a non-equivalent control group design. In this design, the participants are divided into two groups: the experimental group and the control group. Based on the descriptive test results, differences were found in the posttest results between the experimental and control groups. Furthermore, after conducting the N-Gain test, it was found that the learning outcomes of the experimental group were better compared to the learning outcomes of the control group, which received conventional learning. Keywords: cooperative learning model of make a match type, digital flashcards, cognitive learning outcomes